Hand Osteoarthritis: An Update on Therapy - Rashid SAYYID; Imad UTHMAN (Archives of Rheumatology, 2015)
Objectives: This literature review aims to summarize and discuss the most novel clinical studies relevant to the treatment of hand osteoarthritis. Patients and methods: A comprehensive search using Medline and PubMed was performed. Results were restricted to the period between January 2008 and May 2014, and included randomized controlled trials and reviews. The bibliographies of articles retrieved through this search were searched manually for additional relevant references. Results: The latest methods of nerve mobilization, splinting, exercise, and other diverse nonpharmacological treatments have led to significant functional and symptomatic improvements. Topical nonsteroidal antiinflammatory drugs’ clinical beneficence was reinforced and corticosteroid injections were shown to be superior to hyaluronic acid injections. Other pharmacological therapies, such as Hylan injections and synergistic drugs, also showed promise. Antitumor necrosis factor was suggested to play role as a potential disease-modifying agent. Surgical procedures such as arthroscopic debridement, synovectomy of the trapeziometacarpal joint, and early tendon arthroplasty were promising with long-term benefits when used as early interventions. Conclusion: Recent studies show that emerging therapies may play role in the clinical setting as an upgrade over current practices, and that earlier surgical interventions should be considered in the management process.